The Effect of Efflurange Message on Reducing Labor Pain Intensity at Ujungloe Health Center - Alinengsih, Wahyuni; Nabila, Nabila (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Effleurage massage is one of the massages that can reduce the intensity of labor pain. Effleurage massage is done on the back area where massage in that area can relax the muscles, provide a peaceful rest and increase the comfort of the mother during labor. Gentle massage on the back area can play a role in reducing the intensity of labor pain. The purpose of this study was to determine the effect of effleurage massage on reducing the intensity of labor pain in mothers giving birth at the Ujungloe Health Center. This study is a type of quasi-experimental study with the design used is a pretest posttest one group design. This design has a pretest, before being given treatment with a total sample of 18 respondents using total sampling usingWilcoxon testsign rank test.The results of this study were obtained(p value = 0.000 <0.05) then it was found that there was a significant effect of giving effleurage massage in reducing labor pain, it was found that the frequency of back pain in mothers giving birth normally before effleurage massage, the most respondents felt moderate pain as many as 12 respondents (67%) and after effleurage massage, the most respondents felt mild pain as many as 15 respondents (83%). The conclusion of this study is that effleurage massage has an effect on reducing labor pain at the Ujungloe Health Center. This study is expected to provide benefits for the development of obstetrics, one waywhich can be done to reduce labor pain with non-pharmacological actions, furthermore, researchers are expected to provide training to midwives in health centers so that they can be more skilled in carrying out message efflurange to mothers in labor to reduce labor pain.